INTERNALISASI NILAI-NILAI AKHLAK ISLAM DALAM MEMBENTUK KARAKTER SISWA SMA AL-KAUTSAR SUMBERSARI SRONO BANYUWANGI - Mashuri, Imam; Fanani, Ahmad Aziz (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2021)
This study uses a descriptive qualitative type of research. The research was conducted at Sma Al-Kautsar Sumbersari Srono Banyuwangi. Data collection techniques using observations, interviews and documentation. The validity of the data in this study uses triangulation methods and uses descriptive analysis to describe and explain the data obtained. From the results of the research obtained, the process of planting Islamic moral values in shaping the character of students by using 3 stages. First, the stage of value transformation is to provide knowledge and understanding to students. Second, the value transaction stage is by the method of civility and habituation to provide a direct experience to students. Third, the transinternization stage of value is by methods of supervision, advice and reprimand/sanctions. The impact of internalization of Islamic moral values in shaping the character of students in the form of satisfactory academic achievement and the attitude or character of students are increasingly organized.